Softer More Frequent Stools in Infants With Difficult Stooling Fed Hydrolyzed Protein Formula With Added Prebiotics: Randomized Controlled Trial - Fabrizio, Veronica; Harris, Cheryl L.; Walsh, Kelly R.; Wampler, Jennifer L.; Zhuang, Weihong; Wu, Steven S. (Frontiers in Pediatrics, 2022)
Objective: To evaluate stool consistency in infants with reported hard or infrequent stools fed hydrolyzed protein formula with added prebiotics designed to promote stool softening. Methods: In this multi-center, double-blind, controlled study, eligible infants (28-300 days of age at enrollment) were randomized to: partially hydrolyzed cow’s milk protein formula (PHF, 75% carbohydrate as lactose; 12mg Mg/100 kcal; n=49) or routine intact protein cow’s milk-based infant formula (Control, 92% carbohydrate as lactose; 8mg Mg/100 kcal; n=51) over a 14-day period. Both formulas had a prebiotic blend (polydextrose and galactooligosaccharides, 4g/L; 1:1 ratio). Parent-reported stool consistency (hard=1 through watery=5) and other daily outcomes were collected by diary. Endpoint stool consistency (mean score over last three days of study feeding) was the primary outcome. Adverse events were recorded. Results: Baseline stool consistency (Control: 1.4±0.1, PHF: 1.4±0.1) and frequency were similar between groups; the majority had hard (n=61, 64%) or formed (n=30, 32%) stools. Stool consistency became softer over Day 1-3 (Control: 2.5±0.1, PHF: 2.6±0.1) and remained similar from Day 4-6 through study end (post-hoc analysis). For PHF vs Control, endpoint stool consistency was significantly softer (3.4±0.1 vs 3.0±0.1; P=0.019) and frequency significantly higher (1.5±0.1 vs 1.0±0.1; P=0.002). Crying, fussing, and appearance of pain during stooling decreased from baseline to study end in both groups. Formula intake, infant fussiness and incidence of adverse events were similar between groups. Conclusions: An infant formula designed to promote stool softening was well-tolerated and associated with softer, more frequent stools in infants with reported hard or infrequent stools.